Unilateral leukemic infiltration and acute angle closure as the first sign of B-cell acute lymphoblastic leukemia relapse - Silva, Diana; Mota, Mafalda; Bilé, Andreia; Ramalho, Mário; Pinto, Sara; Pires, Graça; Teixeira, Susana; Prieto, Isabel (GMS Ophthalmology Cases, 2019)
Objective: Unilateral ocular leukemic infiltration with acute angle closure is an infrequent complication of B-cell acute lymphoblastic leukemia (ALL-B). We present a clinical case of leukemic ocular infiltration as the sole manifestation of ALL-B relapse.Methods: Case descriptionResults: A 15-year-old female with a history of acute lymphoblastic kemia in remission for 2 years and pulmonary tuberculosis treated in the past year presented with ocular redness and decreased visual acuity in the left eye (LE) with 5 days of evolution. Visual acuity was 20/20 in the right eye (RE) and absence of light perception in the left eye (LE). Biomicroscopy of LE showed a small hypopion, anterior chamber cells 4+, vitreous cells 3+, and a large white mass in the vitreous with associated vitreous hemorrhage in organization. In LE fundoscopy, the vitreous mass occupying most of the vitreous cavity and associated hemorrhage prevented retina visualization. B-scan sound showed a multilobulated mass occupying virtually the entire vitreous cavity with associated choroidal detachment. Forty-eight hours later, she developed acute angle closure of LE with an IOP of 55 mmHg. A flow cytometric analysis of the anterior chamber and vitreous showed leukemic tumor cells. The microbiologic exam and PCR for were negative. No other signs of relapse of the disease were identified after investigation by the oncology department. Rescue treatment of the underlying disease was started, with symptomatic improvement. Conclusion: Leukemic ocular infiltration can be the only manifestation of ALL-B relapse.